Understanding Dhatu Poshan Nyaya in the Light of Stem Cell Theory - Satakshi Chauhan; Anjnee Bijlwan; Apurwa Saini; Shaveta Sawhney (AYUSHDHARA, 2024)
The word Dhatu forms with ‘Dha’ and suffix ‘tin’. It means basic element which helps in construction. A living body comprises of 7 Dhatus (tissue), which not only does Dharan of the body but also provides Poshan or nutrition to the next forming Dhatu. Tissue nutrition is the continuous process which persists throughout the life, but it’s different during different phases of life. Acharayas postulated theories of tissue nutrition and transformation of tissue nutrients into bodily element through Dhatu Poshana Nyaya (tissue nutrition and differentiation theory). The theories of tissue nutrition are Ksheera Dadhi Nyaya (Law of Transformation), Khale Kapot Nyaya (Law of Selectivity), Kedari Kulya Nyaya (Law of Transportation) and Ek Kaal Dhatu Poshan Nyaya (simultaneous supply of nutrients to whole body). This review is an attempt to explore the Ayurveda’s view on tissue differentiation along with physiological and clinical significance of theories of tissue differentiation in a scientific mannery.